TINGKAT KEPUASAN MASYARAKAT PENGUSAHA AGRIBISNIS DALAM PENGURUSAN IJIN PIRT DI DINAS KESEHATAN KOTA BENGKULU - Mutmainnah, Elni; Marwan, Edy (AGRIPITA JOURNAL, 2017)
IRT License is marketing authorization of food production of UKM to be locally marketed. This is an initial step for agribusiness entrepreneur to embark local market which has standard guarantee of food safety. As a result of that license, entrepreneur will easily come through several markets and compete with other food entrepreneurs. This survey has purpose to know about satisfaction level of society especially agribusiness entrepreneur about getting PIRT License at Public Health Service of Bengkulu City. Approach using to specify satisfaction level is according to IKM (Satisfaction Community Index) which consist of (1) Care workers clarity (2)Care workers discipline (3) Care workers responsibility (4) Care workers capability (5) Speed of service (6) Fair service (7) Courtesy and friendliness of workers (8) Service procedure (9) Requirements service (10) Proper-fee service (11) Appropriate-fee service (12) Clarity-schedule service (13) Environment convenience (14) Environment security. Sample of this survey is 30 entrepreneur domestic industry of typical food in Bengkulu City. According to the result of Calculation of Satisfaction Community Index, the quality service at Integrated Licencing Service Board of Bengkulu City is good. However, long and complicated process of getting requirements license that needs more time than necessarily makes process of given license taking protracted time. It will impact less motivation to entrepreneur administering PIRT license.